Pemanfaatan Aplikasi Smartphone untuk Meningkatkan Kemampuan Mengidentifikasi Hipoglikemia di Wilayah Kerja Puskesmas Simpang Kawat - Netha Damayantie; Rusmimpong Rusmimpong; Mashudi Mashudi (Jurnal Abdimas Kesehatan (JAK), 2022)
Hypoglycemia has a serious impact on the morbidity, mortality and quality of life of people with Diabetes Mellitus (DM). To prevent or reduce the risk of hypoglycemia, education is very important, including identification of hypoglycemia, detection of causes, prevention efforts and early treatment efforts at home. The use of mobile applications strongly supports independent health management because it is easily accessible, portable, low cost, convenient for users, and has a wide reach. This community service aims to optimize the use of the smartphone application “NEDTA” to improve the ability to identify hypoglycemia in people with diabetes mellitus in the Simpang Kawat Health Center area of Jambi City. The partners of this Community Partnership Program are the Head of Simpang Kawat Health Center, the Person in Charge of the Non-Communicable Disease Program (PTM) and 40 people with DM who meet the criteria. The methods used include socialization, competency improvement, implementation of activities, monitoring and evaluation. The results of community service revealed that more than half (58%) had diabetes for more than 10 years and most (74%) had experienced hypoglycemia. There was an increase in the ability to identify hypoglycemia after using the NEDTA smartphone application from 40% of high ability patients (pre test) to 75% (post test). The Head of the Community Health Center in charge of the non-communicable disease program at the Simpang Kawat Health Center is expected to continue mentoring activities in the use of the NEDTA application so that DM sufferers are independent in recognizing hypoglycemia, supporting the prevention and eradication of non-communicable diseases (P2PTM) such as diabetes mellitus, hypertension and other non-communicable diseases and support the PIS-PK Program.